Ovarian response and follow-up outcomes in women diagnosed with cancer having fertility preservation: Comparison of random start and early follicular phase stimulation - cohort study. (November 2018) - Muteshi, Charles; Child, Tim; Ohuma, Eric; Fatum, Muhammad
Abstract: Objectives: To determine response to controlled ovarian stimulation in a random start cycle and utilisation of cryopreserved oocytes and embryos in cancer patients. Study Design: A retrospective cohort study was carried out in an assisted reproductive treatment centre. Participants included 137 cancer patients who underwent controlled ovarian stimulation for fertility preservation between 1 Feb 2003 and 30 June 2016. The primary outcome variable was number of oocytes retrieved. Multivariable logistic regression analysis was performed, and differences compared using Chi squared test and student t -test as appropriate. P < 0.05 was considered statistically significant. Results: Using the antagonist protocol, there was no difference in number of oocytes retrieved between the early follicular phase or at random start stimulation; 11.9 (95% CI 10.3–13.5) and 12.9 (95% CI 9.6–16.2), P = 0.602, respectively. Similarly, the number of embryos frozen was comparable between those starting stimulation in early follicular and random phase, 6.7 (95% CI 5.7–7.7) and 5.1 (95% CI 3.6–6.5), P= 0.1508 respectively. Among patients undergoing fertility preservation, those who returned to attempt a pregnancy had an ongoing pregnancy rate of 24.3%. Overall, 65% of oocytes and embryos were still in storage, however, 16 (11.7%) had elected to have their oocytes or embryos disposed of. Conclusion(s): For women faced with potential gonadotoxic treatment and requiring urgent fertility preservation, ovarian stimulation with the antagonist protocol can be started at random without compromising ovarian response. Pregnancy rates following utilisation of frozen-thawed oocytes and embryos are promising, however, more research is needed to understand reasons underlying disposition of oocytes and embryos especially when survival following cancer treatment has improved significantly.